Nesfatin-1 Promotes the Osteogenic Differentiation of Tendon-Derived Stem Cells and the Pathogenesis of Heterotopic Ossification in Rat Tendons via the mTOR Pathway - Xu, Kai; Zhang, Zhanfeng; Chen, Mengyao; Moqbel, Safwat Adel Abdo; He, Yuzhe; Ma, Chiyuan; Jiang, Lifeng; Xiong, Yan; Wu, Lidong (Frontiers in Cell and Developmental Biology, 2020)
Tendinopathy in patients with diabetes mellitus (DM) has attracted substantial attention. There is a growing body of evidence that DM is a prominent risk factor for the pathogenesis of tendinopathy, but the detailed mechanisms remain unknown. Nesfatin-1 is an 82-amino acid adipokine. It has been previously demonstrated that this peptide is closely related to DM. In the present study, we aimed to investigate the effects of Nesfatin-1 on the osteogenic differentiation of tendon-derived stem cells (TDSCs) and the pathogenesis of heterotopic ossification (HO) in rat tendons. In vitro, TDSCs were incubated in osteogenic induction medium for 14 days with different concentrations of Nesfatin-1. In vivo, Sprague-Dawley rats underwent Achilles tenotomy to evaluate the effect of Nesfatin-1 on tendinopathy. Our results showed that the expression of Nesfatin-1 in tendinopathy patients was significantly higher than that in healthy people. Nesfatin-1 inhibited the expression of Scx, Mkx and Tnmd and promoted the expression of osteogenic genes, such as COL1a1, ALP and RUNX2; these results suggested that Nesfatin-1 promotes the osteogenic differentiation of TDSCs and the pathogenesis of HO in rat tendons. Furthermore, we found that Nesfatin-1 suppressed autophagy and activated the mTOR pathway both in vitro and in vivo. The suppression of the mTOR pathway alleviated Nesfatin-1-induced HO development in rat tendons. Thus, Nesfatin-1 promotes the osteogenic differentiation of tenocyte progenitor cells and the pathogenesis of HO in rat tendons via the mTOR pathway; these findings provide a new potential therapeutic target for tendinopathy.